The Cost Dynamics of Tuberculosis Comprehensive Programme: A Systematic Review - Lestyoningrum, Sinta Dewi; Noveyani, Adistha Eka; Putro, Wahyu Gito; Nugraheni, Wahyu Pudji; Faisal, Debri Riski; Pawitaningtyas, Indah; Mikrajab, Muhammad Agus (Malaysian Journal of Medical Sciences, 2026)
Tuberculosis (TB), as a significant global health challenge, remains leading the increasing burden of its disease. There is an essential requirement to understand and manage the costs of the TB treatment programme to ensure the sustainability of the TB control programme. The aims of this study are to synthesise existing literature on the economic implications of TB treatment programmes, focusing on the cost of the programme associated with drug-susceptible and drug-resistant TB. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and utilising the Population, Intervention, Comparison, Outcomes, and Study Design (PICOS) framework, studies published from 2013 to 2024 were systematically searched from PubMed, Scopus, and ScienceDirect. Only economic evaluations were included, resulting in 11 articles that provided diverse regional insights into TB costs. The review highlights the considerable financial burden of TB’s management, with diverse results from the literature. This study reveals that the combined strategy of the TB programme increases the cost-effectiveness at USD9,050.00 per disability-adjusted life year (DALY) and USD443.62 per TB case. The highest cost of the TB programme was reported for the passive case finding (PCF) at USD226.13 for adults. The funding gap was reported at USD301.62 million from 2018 to 2022. Effective TB management requires some comprehensive financial strategies to mitigate the economic burden that affects the direct and indirect national expenditure. Focusing on combining the strategies of passive and active case finding, increasing the treatment’s accessibility, and supporting the drug innovation are believed to be the strategies to enhance the achievement of the TB programme, as well as increasing the cost-effectiveness of its programme.